'Double‐Hit' cytogenetic status may not be predicted by baseline clinicopathological characteristics and is highly associated with overall survival in B cell lymphoma patients. (25th April 2014) - Landsburg, Daniel J.; Nasta, Sunita D.; Svoboda, Jakub; Morrissette, Jennifer J. D.; Schuster, Stephen J.
Summary 'Double‐Hit' (DH) B cell non‐Hodgkin lymphomas are characterized by the presence of a MYC rearrangement and additional rearrangement(s) most commonly involving BCL2 and/or BCL6. Patients with DH lymphomas are unlikely to achieve long‐term survival when treated with standard immunochemotherapy alone. DH gene rearrangements can be identified through metaphase karyotyping or more sensitive fluorescence in situ hybridization (FISH), although the latter is not routinely performed. We report 53 cases of B cell lymphoma that underwent diagnostic metaphase karyotying or FISH for MYC rearrangements. DH lymphoma was detected in 17 cases. No baseline factor, including age, serum lactate dehydrogenase, stage, International Prognostic Index or histology predicted for DH status. The median overall survival was significantly shorter for DH compared to non‐DH lymphoma patients (8·2 vs. 56·8 months, P < 0·001). DH status retained the most statistically significant association with overall survival on multivariate Cox regression analysis. DH status could not be inferred by baseline disease‐ or patient‐related characteristics and was most predictive of overall survival in this cohort of B cell lymphoma patients. These findings support the practice of routine performance of FISH for DH gene rearrangements on B cell lymphoma specimens in order to effectively identify DH patients who may benefit from risk‐adapted therapy.